Pengembangan Media Transpor untuk Koleksi Sampel Preputium, untuk deteksi Bovine Genital Campylobacteriosis - Apris Beniawan; Agustin Indrawati; Fachriyan Hasmi Pasaribu (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2020)
Campylobacter fetus subsp. Venerealis (Cfv) is bacteria causing contagious genital diseases in cows called Bovine Genital Campylobacteriosis (BGC) or vibriosis. Isolation of Cfv is difficult, because the bacteria are fragile and need specific nutrients and oxygen (5-10%). The transport media is very important to maintain Cfv survival before culturing in laboratory. The aim of this study was to modify a new transport media as an alternative media for Cfv. Developed media capability was compared to Weybridge media, and Phosphate Buffered Saline (PBS). All transport media was contaminated by Cfv with concentrations of 105,104,103,102,101 (CFU/ml), and was stored for <6, 24, 48, 72, and 96 hours in each transport medium before culturing on blood agar, all in triplicate. The quality of transport media was analyzed based on bacterial growth on blood agar. PCR test was used as a confirmatory test of growing bacteria cultured on blood agar. Based on culture results, Cfv stored in three transport mediums for <6 hours, Cfv grew on blood agar from all concentration levels provided. Cfv stored for 24, 48, 72 and 96 hours on PBS did not grow, whereas on developed media and Weybridge media, the bacteria could grow and enrichment occurs at all concentration levels given. This study indicated the developed media can be used as an alternative transport medium for Cfv bacteria.